Analisis Pemikiran Tokoh-Tokoh Sosiologi Hukum dalam Perspektif Hukum dan Masyarakat - Derma Pratiwi, Nabia Dilla; Soraya, Della; Mabilla, Anung; Septiani, Reni Mulia; Pratiwi, Rizki Septia; Anggraini, Nur Hidayah; Susilo, Susilo; Saputri, Rima Yuni (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze the thoughts of prominent figures in the sociology of law from the perspective of the relationship between law and society. This research is motivated by the importance of understanding law not only as a set of written norms, but also as a dynamic social phenomenon influenced by various aspects of social life. The study employs a qualitative approach with a descriptive research design using library research methods. Data were collected from relevant literature, including books, academic journals, and scholarly works, and were analyzed using a descriptive-analytical method. The findings reveal that scholars such as Roscoe Pound, Soerjono Soekanto, Satjipto Rahardjo, and others have made significant contributions to the development of legal sociology by positioning law as a social institution that functions not only as a tool of social control but also as an instrument of social engineering. Their perspectives emphasize the reciprocal relationship between law and society, where law is shaped by social values, culture, and dynamics, while simultaneously playing a role in achieving justice, order, and social welfare. Therefore, the sociological approach to law is essential in understanding the effectiveness and relevance of law in modern society. Keywords: Sociology of Law, Law and Society, Legal Thinkers, Social Change, Legal Effectivenes